DIGISEKSUAL DAN PENANGGULANGANNYA BERBASIS AL-QUR’AN - Nurbaiti Nurbaiti (el-'Umdah, 2020)
Conclution of the research explains about digisexual and the prevention based on the Qur’an. Digisexual is a behavior sexual gratification with sexual objects or sex partners in the form of technology or digital. Digisexual is an abnormal behavior, which requires countermeasures to prevent and treat it. In this research, the prevention of the digisexual problem based on the Qur’an becomes one of the proofs that the Qur’an responds to various phenomena and human problems that develop, one of them is the problem of digisexual. Qur’an as kalamullah, responds to the problem of digisexual, both Qur’an as Hudâ or guidance, Adz-Dzikir or reminder, and gives solution. The interpretation method used in this research ismaudhu’Imethod or the thematic combined with qualitative methods based on library research, Qur’an verses, publications in the form of research results, journal, conference proceedings or seminars and articles.